Effect of Mean Platelet Volume on Outcome of Stroke Infark in Elderly Patient - Anita Rosari Dalimunthe; Probosuseno; I Dewa Putu Pramantara (Sumatera Medical Journal, 2025)
Background: Hyperreactivity and activation of platelet play a role in the occurrence and severity of ischemic stroke in geriatric patients. Mean Platelet Volume (MPV) describes levels of stimulation as well as platelet production rates that may affect the incidence of ischemic stroke and its clinical outcome. Objective: To determine the effect of MPV on the outcome of stroke infarction in geriatric patients. Methods: This was a cohort study. MPV measured at hospital admission. Statistical analysis carried out by Receiver of Curve (ROC) test to determine the MPV cut off point and Chi-square to determine the relationship between MPV and infarction of stroke patient using SPSS v.22. Results: There were 52 stroke patients with mean age 68.25+6.06 years. Clinical outcomes   deteriorated in 38 (73.08%) patients. The AUC value of MPV was 73.3% (p=0.011) with MPV cut off point 10.85fl. Deterioration occurred in 10 (43.38%) patient with MPV >10.85fl. The Chi-square test result was (p<0.001) showing a difference between the groups (RR 3.125 CI 95% 1.134-8.761). Conclusion: Ischemic stroke patients with MPV levels >10.85fl at hospital admission had 3 times chance of deterioration. MPV can be used as prognostic factor for clinical outcome of acute ischemic stroke in geriatric patients.